2017
DOI: 10.1113/jp273484
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status‐dependent endocannabinoid signalling regulates the integration of rat visceral information

Abstract: Communication form the viscera to the brain is essential to set physiological homoeostatic parameters but also to drive more complex behaviours such as mood, memory and emotional states. Here we investigated the impact of the nutritional status on long-term changes in excitatory synaptic transmission in the nucleus tractus solitarii, a neural hub integrating visceral signals. These excitatory synapses exhibit a CB1 endocannabinoid (eCB)-induced long-term depression (LTD) triggered by vagal fibre stimulation. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…For instance, Xia et al showed that miR-384-3p inhibited retinal neovascularization during diabetic retinopathy [48]. KEEG analysis also revealed that the miRNAs of interest control activity-dependent synaptic plasticity, such as long-term potentiation (LTP) and LTD. Interestingly, several studies highlighted that energy state may control the LTP as well as LTD [49,50]. Particularly, a tetanic stimulation protocol induced LTD at POMC neurons in fed mice but weak LTP in food-deprived mice [50].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Xia et al showed that miR-384-3p inhibited retinal neovascularization during diabetic retinopathy [48]. KEEG analysis also revealed that the miRNAs of interest control activity-dependent synaptic plasticity, such as long-term potentiation (LTP) and LTD. Interestingly, several studies highlighted that energy state may control the LTP as well as LTD [49,50]. Particularly, a tetanic stimulation protocol induced LTD at POMC neurons in fed mice but weak LTP in food-deprived mice [50].…”
Section: Discussionmentioning
confidence: 99%
“…Following fasting, elevated ghrelin levels impair eCB-mediated LTD, which can be restored by the elevation of CCK. This mechanism can be thought of as an integrator between visceroafferents and blood-borne signals: the humoral satiety signal CCK attenuates neuronal transmission while the “hunger hormone” ghrelin leads to a more reliable conveyance of afferent signals [ 117 ]. Both humoral and neuronal pathways are linked by eCBs, underlining their importance as local modulators, especially in feeding circuits.…”
Section: Endocannabinoids In Central Control Of Body Weightmentioning
confidence: 99%